Analysis of infragravity waves characteristics and energy evaluation based on field observations - Xiang Gao; Zhongbo Hu; Jianhong Jiang; Yueguang Jiang (Frontiers in Marine Science, 2025)
The characteristics and energies of infragravity waves (IGWs) are investigated based on field observations. IGWs are closely related to short waves, and the wave spectrum integration method was adopted to separate sea and swell waves. By comparing the performance of the separation frequency in the spectral shape and the correlation between the IGWs and short waves, it was found that the dynamic separation frequency was more reasonable than the commonly used fixed separation frequencies (0.125 and 0.14 Hz). Infragravity waves exhibited a stronger correlation with swell than with wind waves, with a correlation coefficient exceeding 0.8. Therefore, swell wave heights were used instead of short-wave heights for the energy evaluation of the IGWs. The spectral domain method was adopted to separate the incident and reflected IGWs, and, combined with the bound infragravity waves (BIG), was used to obtain the wave height of each IGW component. The wave heights of the BIG and swell exhibited a significant quadratic relationship. The correlation between the free infragravity waves (FIG) and swell was weaker than that of the BIG. An empirical expression between the wave heights of total incident IGWs and the swell waves was obtained, and the exponent α related to swell wave heights was approximately 1.0.